STRATEGI MARGINALISASI MELALUI WACANA SEBAGAI PRAKTEK SOSIAL DALAM BAHASA INDONESIA - Fransiskus Sanda; Fransiskus Bustan; Alexander H. Kabelen (Jurnal Lazuardi, 2020)
This study describes and explains marginalisation strategy through discourse as social practice in Indonesian language, as reflected in language behavior appearing in the form of euphemism, disphemism, labelisation, and stereotype, one the basis of library research. The result of study shows that marginalisation strategy through discourse as social practice in Indonesian language designates the power dominance of upper level social class towards lower level social class. The manfestation of the marginalisation strategy is stated and implied in the use of the following words or terms (a) ;pemutusan hubungan kerja’ replacing ‘pemberhentian’ or ‘pemecatan’ (euphemism) in economy discourse, (b) ‘pencaplokan’ or ‘penyerobotan’ with the conotation of negative meaning (diphemism) in political discouse, (c) ‘penggarap liar’ and ‘penyerobot lahan’ with the negative meaning (labelisation) in political discourse, and (d) ‘perempuan’ with the negative meaning and ‘wanita’ with the positive meaning (stereotype) in social and cultural discourse .